2015
DOI: 10.1016/j.actbio.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Intramyocardial injection of hydrogel with high interstitial spread does not impact action potential propagation

Abstract: Injectable biomaterials have been evaluated as potential new therapies for myocardial infarction (MI) and heart failure. These materials have improved left ventricular (LV) geometry and ejection fraction, yet there remain concerns that biomaterial injection may create a substrate for arrhythmia. Since studies of this risk are lacking, we utilized optical mapping to assess the effects of biomaterial injection and interstitial spread on cardiac electrophysiology. Healthy and infarcted rat hearts were injected wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 50 publications
0
26
0
1
Order By: Relevance
“…Both the direct infarct injection [8][9][10] and BZ injection [39][40][41] have shown functional benefits experimentally. To our knowledge, an experimental comparison of these two injection strategies has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Both the direct infarct injection [8][9][10] and BZ injection [39][40][41] have shown functional benefits experimentally. To our knowledge, an experimental comparison of these two injection strategies has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The cell density in the hydrogel group was ~6.0 times and ~16.9 times of collagen and PBS groups, respectively. One of the concerns in using fast gelling hydrogels is that the formed bolus may disrupt electrical conductivity in the heart tissue [87]. However, the hydrogels will be injected into the infarcted region where electrical conductivity is very low.…”
Section: Discussionmentioning
confidence: 99%
“…Principal component analysis and pathway analysis showed that alterations in pathways associated with the inflammatory response (Figure 4), cardiomyocyte apoptosis, infarct neovascularization, cardiac hypertrophy and fibrosis, metabolic enzyme expression, cardiac transcription factor expression, and progenitor cell recruitment all may have contributed to cardiac functional improvement [68]. Suarez et al explored the influence of biomaterial injection on action potential propagation across the heart [69]. PEG hydrogels were injected into healthy and infarcted rat hearts as a model material and were found to delay action potential propagation across the LV epicardium compared to saline injection and sham controls [69].…”
Section: Mechanisms Of Biomaterials Injection Therapy and Influence Ofmentioning
confidence: 99%
“…Suarez et al explored the influence of biomaterial injection on action potential propagation across the heart [69]. PEG hydrogels were injected into healthy and infarcted rat hearts as a model material and were found to delay action potential propagation across the LV epicardium compared to saline injection and sham controls [69]. In addition, it was found that a highly diffused hydrogel does not alter action potential propagation, while a hydrogel that did not spread as extensively would reduce gap junction densities and may create a substrate for arrhythmias [69].…”
Section: Mechanisms Of Biomaterials Injection Therapy and Influence Ofmentioning
confidence: 99%
See 1 more Smart Citation